2012
DOI: 10.1002/app.38715
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization and thermomechanical properties of PLA composites: Effects of additive types and heat treatment

Abstract: This research work has concerned a study on thermomechanical and crystallization properties of poly(lactic acid) (PLA) composites containing three different types of additives; namely: kenaf fiber (20 pph), Cloisite30B nanoclay (5 pph), and hexagonal boron nitrile (h-BN; 5 pph). The composites were prepared using a twin screw extruder before molding. Crystallization behaviors of the various composites were also examined using a differential scanning calorimetry. By adding the additives, tensile modulus of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 26 publications
4
48
0
Order By: Relevance
“…20,22,23 However, in the current study, ANOVA results showed no statistically significant difference in strength or elastic modulus for samples subjected to different annealing conditions. This may be partially due to the 3D-printed structure of the specimens, which has been shown to produce lower tensile properties than equivalent injection molded parts.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…20,22,23 However, in the current study, ANOVA results showed no statistically significant difference in strength or elastic modulus for samples subjected to different annealing conditions. This may be partially due to the 3D-printed structure of the specimens, which has been shown to produce lower tensile properties than equivalent injection molded parts.…”
Section: Discussionmentioning
confidence: 45%
“…[18][19][20][21][22][23] The low degree of crystallinity of the as-received filament and as-printed samples can be attributed to relatively rapid cooling of the experienced by the polymer, which does not allow enough time for any significant crystallization to occur, due to the slow nucleation and crystallization rates of PLA. 17,24,25 For the as-received filaments, this rapid cooling would have occurred during the extrusion process, while for the as-printed specimens, the rapid cooling is experienced due to the cooling fans used to solidify the polymer after it has been deposited.…”
Section: Discussionmentioning
confidence: 99%
“…The heat of fusion was calculated by integrating the areas under the endothermic curves. The crystallinity of the HDPE phase was calculated by using Equation 1 [16]. …”
Section: Differential Scanning Calorimetry Analysismentioning
confidence: 99%
“…Starch/PLA blends have been reported where PLA enhances the tensile strength of the blend, while it decreases the moisture uptake compared to starch alone[48][49][50][51]. Wootthikanokkhan et al[52] report PLA/maleated thermoplasctic starch (MTPS) blends, which show an increase in tensile strength, elongation-atbreak, modulus and toughness with an increase in the amount of PLA from 60% to 80%. They also note the effect of blending temperature and time on the mechanical properties of the blend, where the strength and modulus increase while elongation-at-break and toughness decrease with an increase in blending time and temperature.…”
mentioning
confidence: 96%